Discourse Markers in the Students’ Individual Presentation in Indonesian Classroom - Murni Mahmud; Abdul Halim; Sahril Nur (State University of Makassar, 2023)
Individual presentation is one of common presentations used by students to present certain topic given by the lecturers in the class. This kind of presentation may take place in a range of setting such as in the classroom by providing question-and-answer session. Individual presentation might also invite classroom interaction among the students. One specific aspect of individual presentation which may contribute to the effective classroom interaction is the use of discourse markers by the students. This paper focuses to investigate the functions of discourse markers used by the students in the individual presentation as well as the students’ interaction during the presentation. Using data from an English class, this study describes the occurrences of discourse markers (DMs) used by the students in their individual presentations. To collect data, the researchers recorded individual presentations of the students in the class. Two long recording and transcription of the individual presentations was sampled and analyzed using discourse analysis approach. The discourse markers used by the students were analyzed using Schiffrin’s perspective of discourse markers (1987). Findings show that the students’ most common use of discourse markers function as pause filler, delaying tactic, hesitation device, to order the sequence of what the speaker says. Findings of this study are relevant to improve students’ English language proficiency and serves as a beneficial input for teachers and students to create effective classroom interaction.Keywords: Individual Presentation, Discourse Markers, Discourse Analysis, Scriffin’s discourse makers (DMs) perspective